Differences in immunomodulatory properties between venlafaxine and paroxetine in patients with major depressive disorder. (January 2018) - Chen, Chun-Yen; Yeh, Yi-Wei; Kuo, Shin-Chang; Liang, Chih-Sung; Ho, Pei-Shen; Huang, Chang-Chih; Yen, Che-Hung; Shyu, Jia-Fwu; Lu, Ru-Band; Huang, San-Yuan
Highlights: Venlafaxine and paroxetine have different immunomodulatory properties. Venlafaxine has greater anti-inflammatory effects than paroxetine. IL-6 levels increased more in the non-remitter group than in the remitter group after paroxetine treatment. After venlafaxine treatment in both the remitter and non-remitter groups, IL-1β levels decreased to values seen in the healthy controls. Abstract: Inflammatory processes play a crucial role in the pathophysiology of depression, and identifying the specific cytokines targeted by different antidepressants is important for personalized treatment. The aims of this study were to examine whether venlafaxine and paroxetine cause different immunomodulatory effects when used to treat patients with major depression and to clarify the relationships between plasma cytokine levels and the therapeutic effectiveness of these drugs. A total of 91 Han Chinese patients with major depression completed the 8-week paroxetine or venlafaxine treatment and 90 healthy controls were recruited. A multiplex assay was used to measure cytokines levels in patients with major depression before and after an 8-week venlafaxine and paroxetine treatment. Cytokine levels were measured in healthy controls at the baseline. The 21-item Hamilton Depression Rating Scale was used to assess the changes in psychopathological symptoms from the baseline to the end point in each patient. Venlafaxine treatment caused greater decreases in the levels of interferon gamma (IFN-γ), tumor necrosis factor alpha (TNF-α), interleukin 4 (IL-4), IL-5, IL-1β, and IL-8 than did paroxetine. Paroxetine treatment increased the levels of proinflammatory cytokines IFN-γ, TNF-α, and IL-6 and decreased Th2 cytokine levels. After paroxetine treatment, IL-6 levels increased more in the non-remitter group than in the remitter group. In the remitter group, IL-4 and IL-5 levels decreased to values seen in the healthy controls. After venlafaxine treatment in both the remitter and non-remitter groups, IL-1β levels decreased to values seen in the healthy controls. Our results suggest that venlafaxine and paroxetine have different immunomodulatory properties and that venlafaxine has greater anti-inflammatory effects than paroxetine.